(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
Studying the history of the office of the Turkestan governors-general is a very interesting research problem. For a more complete understanding of the essence of the work of the office, which, when exercising its executive powers in Turkestan, was not accessible to the bulk of officials in the system of military-people’s government, not to mention ordinary ordinary employees. For the historical reconstruction of the sphere of activity and structure of the office of the Turkestan governors-general, the main priority belongs to written sources of the second half of the 19th – early 20th centuries.